Producer’s culture and standards of living as causes for the growth of the innovative globalized economy - Serazhym , Yu.V. (Ways to Improve Construction Efficiency, 2020)
The article examines current aspects of the development of human potential, both in economic and cultural contexts. The author links L. Vygotsky’s conceptualization of social development dynamics with M. Max-Neef’s development model based on the research into producers’ fundamental needs. Such combination has helped to identify a correlation between cultural and physical needs of a person with the dynamics of person’s intellectual potential growth, as well as the former’s key role in alleviation of poverty. With the modern development of innovative economy, there is inevitably a need for a new cultural vision of the market role in accordance with the needs of harmonious development of the individual. This vision should be focused not so much on the increase in additional value, but on the presence of the necessary signs in public life caused by the level of quality of life of the employee. It is revealed that the modern international economic order is the source of human poverty, and at the same time various social problems, and the source of problems related to the individual, given the triad of economy-society-culture. Without the dialectical unity of economic development of society and the development of the employee's personality, the chances of survival of the individual and society become infinitesimal and at the same time there is a tendency to degrade the cultural heritage of mankind. Thinking and rethinking the design of any social development-oriented tool, especially in the community, should be multidimensional in nature and include well-connected control phases. Failure to do so can lead to imbalances and gaps between the scientist's theoretical vision and the contextual reality that is changing. The article shows various aspects of the role of dialectical unity of economic development of society and development of the employee's personality, without which the possibility of survival of a person and society becomes infinitely small and at the same time there is a tendency to degrade the cultural heritage of mankind.